PagERF16 of Populus Promotes Lateral Root Proliferation and Sensitizes to Salt Stress - Wang, Shengji; Huang, Juanjuan; Wang, Xingdou; Fan, Yan; Liu, Qiang; Han, Youzhi (Frontiers in Plant Science, 2021)
The aggravation of soil salinization limits the growth and development of plants. The AP2/ERF transcription factors (TFs) have been identified and play essential roles in plant development and stress response processes. In this study, the function of PagERF16 was detected using the overexpressing (OX) and RNAi transgenic poplar 84K hybrids. Plant growth, stomatal conductance, antioxidant enzymes activity, and PagERF16 co-expressed TFs were analyzed using morphological, physiological, and molecular methods. OX showed a more robust lateral root system with a bigger diameter and volume compared to the wild-type plants (WT). Physiological parameters indicated the bigger stomatal aperture and lower stomatal density of OX along with the lower Catalase (CAT) activity and higher malondialdehyde (MDA) content contributed to the salt sensitivity. The plant height and rooting rate of OX and RNAi were significantly worse compared to WT. Other than that, the morphology and physiology of RNAi plants were similar to WTs, suggesting that the function of PagERF16 may be redundant with other TFs. Our results indicate that when PagERF16 expression is either too high or too low, poplar growth and rooting is negatively affected. In addition, a downstream target TF, NAC45, involved in Auxin biosynthesis, was identified and PagERF16 could directly bind to its promoter to negatively regulate its expression. These results shed new light on the function of ERF TFs in plant root growth and salt stress tolerance.